CLINICAL FEATURES OF PATIENTS WITH PERMANENT PACEMAKERS DEPENDING ON THE STAGE OF ARTERIAL HYPERTENSION - Derienko, T.; Volkov, D. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
The study included 131 patients (70 men and 61 women) aged 69,5 ± 11,6 years who underwent permanent pacing because of atrio-ventricular block(AV), permanent atrial fibrillation(AF) and sick sinus node syndrome(SSS) with pacing modes DDD/DDDR and VVI /VVIR as well as chronic heart failure (CHF) with cardiac resynchronization therapy (CRT-P and CRT-D). Clinical features of patients were evaluated according to the stage of arterial hypertension (AH). The results showed that all patients with implanted pacemakers had hypertension the II and III stages with their ratio 1:2.5. Stable angina, diabetes mellitus (DM), AF, heart failure (HF) II A and moderate degree of AH were associated with the II stage of AH. The III stage of AH was associated with persistent AF and postinfarction cardiosclerosis, while the frequency of occurrence moderate and severe degree of AH were the same. The high frequency of AH in patients with implanted pacemakers and their relationship with other disorders in the health of patients, requires optimization of blood pressure control.